2012
DOI: 10.3402/gha.v5i0.19120
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of developing an instrument to assess health provider motivation at primary care level in rural Burkina Faso, Ghana and Tanzania

Abstract: BackgroundThe quality of health care depends on the competence and motivation of the health workers that provide it. In the West, several tools exist to measure worker motivation, and some have been applied to the health sector. However, none have been validated for use in sub-Saharan Africa. The complexity of such tools has also led to concerns about their application at primary care level.ObjectiveTo develop a common instrument to monitor any changes in maternal and neonatal health (MNH) care provider motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…They conclude that a short list of simple questions can provide significant information on the motivation of health workers across a wide variety of settings. Prytherch et al (2012) test similar instruments and come to a similar conclusion: complexity and nuance are not useful in such surveys. Out of a list of 23 statements (table 8.2), they suggest a reduced list of nine questions in three domains (marked by a plus sign in table 8.2): organizational commitment, job satisfaction, and conscientiousness.…”
Section: Motivation Surveysmentioning
confidence: 82%
See 1 more Smart Citation
“…They conclude that a short list of simple questions can provide significant information on the motivation of health workers across a wide variety of settings. Prytherch et al (2012) test similar instruments and come to a similar conclusion: complexity and nuance are not useful in such surveys. Out of a list of 23 statements (table 8.2), they suggest a reduced list of nine questions in three domains (marked by a plus sign in table 8.2): organizational commitment, job satisfaction, and conscientiousness.…”
Section: Motivation Surveysmentioning
confidence: 82%
“…Low effort may, for instance, involve spending more time than necessary per task (time inefficiency). Prytherch et al 2012. Note: The plus sign (+) signifies a way to reduce the list of 23 statements to nine questions in three domains: organizational commitment, job satisfaction, and conscientiousness.…”
Section: Three-factor Model Of Health Worker Productivitymentioning
confidence: 99%
“…There are several studies on general aspects of HCPs in industrial countries and even some in so-called developing countries (Fischer and Lun 2008;Maestad and Torsvik 2008;Mutizwa-Mangiza 1998;Prytherch et al 2012). Studies that focus systematically on aspects of HCPs in the context of MHOs are sparse: Criel et al indicated, through semi-structured interviews with 16 HCPs in GuineaConakry, difficulties between MHOs and HCPs.…”
Section: Introductionmentioning
confidence: 99%
“…HW motivation may also be influenced by the disproportionate funding, resourcing, infrastructure and historical focus on HIV that have been described in some contexts [27]. Motivation of HWs in developing countries to engage in recently introduced programmes and practices has also been highlighted in the literature to be an important component of programme success [28,29]. Given the complexity of rolling out adult MC programmes that has already been described in Africa, understanding HW motivation in the context of sexual reproductive health services and application to MC programme roll-out is important for policy development.…”
Section: Introductionmentioning
confidence: 99%